34. Burst-suppression with highly epileptiform bursts and with identical bursts: two subtypes within burst-suppression pattern. Issue 12 (December 2016) - Spalletti, M.; Carraia, R.; Scarpino, M.; Cossu, C.; Ammannati, A.; Peris, A.; Valente, S.; Grippo, A.; Amantini, A.
Abstract : Objective is to identify and compare EEGs showing burst-suppression (BS) with identical bursts and BS with highly epileptiform bursts and their prognostic value in a cohort of postanoxic patients. In a retrospective cohort of postanoxic patients who underwent EEG, we selected all patients with BS (ACNS terminology, 2013) at 12 and 24 h after cardiac arrest and classified as having identical bursts and/or highly epileptiform bursts. Outcome was evaluated at 6 months with GOS and dichotomized as good (GOS = 3–5) or poor (GOS = 1–2). Ten patients with BS were identified at 12 h: two had highly epileptiform bursts and identical bursts, one had highly epileptiform bursts, one had identical bursts, and six had 'conventional' BS. At 24 h 11 patients with BS were observed: one had highly epileptiform bursts and identical bursts, three had identical bursts and seven had 'conventional' BS. As a whole all patients with BS had poor outcome, except for one with 'conventional' BS at 12 h. Identical bursts and highly epileptiform bursts can both coincide or appear independently, either way they were invariably associated to poor outcome. Significance-BS with identical bursts and BS with highly epileptiform bursts appear two distinct subtypes of BS which is in itself highly prognostic for poor outcome.